Critical success factor and barriers in implementation of total productive maintenance - Ghirubaagiri Kanesvaran, author; Norhayati Mohmad Zakwan @Zakuan; Fakulti Pengurusan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2018